1992
DOI: 10.1002/bjs.1800790733
|View full text |Cite
|
Sign up to set email alerts
|

Role of congenital hypertrophy of the retinal pigment epithelium in the predictive diagnosis of familial adenomatous polyposis

Abstract: A study was carried out to evaluate congenital hypertrophy of the retinal pigment epithelium (CHRPE) as a disease marker in a defined population with familial adenomatous polyposis (FAP). Indirect ophthalmoscopy was performed on 75 individuals from 25 known families with FAP, of whom 32 were known to be affected and 43 were at a 50 per cent prior risk of developing the disease. A further ten individuals from five families with hereditary non-polyposis colorectal cancer (HNPCC) were also tested. CHRPE was seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…But in some patients with FAP, CHRPE occurs as multiple bilateral lesions. The reported incidence of CHRPE in FAP kindreds ranges from 66 to 92% [6,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 98%
“…But in some patients with FAP, CHRPE occurs as multiple bilateral lesions. The reported incidence of CHRPE in FAP kindreds ranges from 66 to 92% [6,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 98%
“…The diagnostic criteria with the highest specificity/sensitivity for CHRPE include the detection of four small pigmented lesions, or two lesions of which one is large (> 25% of disc surface), using bilateral lens fundoscopic examination [35] . The presence of multiple bilateral lesions appears to be a highly specific marker for FAP (95%-100% specificity) [36] . This makes ophthalmological examination an attractive noninvasive and early diagnostic test for at-risk family members, aside from genetic testing.…”
Section: B A1 A2mentioning
confidence: 97%
“…Seven patients with familial colorectal neoplasia had multiple areas of CHRPE compared with one with sporadic disease (P = 0.02) and one control subject (P = Berk et al, 1988;Chapman et al, 1989;Burn et al. 1991;Giardiello et al, 1991;Morton et al, 1992). Not infrequently, normal individuals have one or two areas of CHRPE (Chapman et al, 1989;Burn et al, 1991), and therefore it is thought to be the presence of multiple areas which is of significance.…”
mentioning
confidence: 99%
“…The gene for FAP has been localised to 5q21 (Bodmer et al, 1987), and a variety of polymorphic DNA markers are available (Nakamura et al, 1988;Meera Khan et al, 1988;Dunlop et al, 1990Dunlop et al, , 1991 family syndrome. Morton et al (1992) found CHRPE in five of ten individuals who were members of five hereditary nonpolyposis colorectal cancer families, however none of these individuals met the authors' criteria for a positive test. Sondergaard et al (1985) identified multiple mandibular osteomata in 8 of 31 (26%) individuals with familial colorectal cancer, however these individuals were all members of two large families.…”
mentioning
confidence: 99%